SISTEM INFORMASI PENDATAAN NARAPIDANA PADA LAPAS MENGGUNAKAN WEB - Imam Hidayat; Andi Wapa; Harun Arrasyid (Lembaga Pengembangan Kinerja Dosen, 2022)
Every institution has important data that must be maintained its authenticity and integrity for the smooth performance of the institution. Both primary and secondary data. Because data collection is the most important part in any job. Meanwhile, in Kraksaan Prison, the data collection mechanism used is still inefficient because it inputs data twice. Namely with a notebook related to the identity of the inmate, and re-sorted into Microsoft Excel. Therefore, this study intends to facilitate prisons in tabulating data, the formulation of the problem in this study is how to make an information system application for data collection of prisoners in prisons using the web, the research method used in this study is a qualitative method. While the system development method in this study uses the waterfall method by conducting observations, interviews, and literature studies. The result of this research is the creation of an information system application for data collection of prisoners in prisons using the web, which aims to facilitate correctional officers in tabulating data. With the implementation of this data collection information system, it is expected to be able to handle problems in the agency, namely facilitating data collection and printing reports.